Cytoplasmic HDAC4 regulates the membrane repair mechanism in Duchenne muscular dystrophy. Issue 2 (15th February 2022) - Renzini, Alessandra; Marroncelli, Nicoletta; Cavioli, Giorgia; Di Francescantonio, Silvia; Forcina, Laura; Lambridis, Alessandro; Di Giorgio, Eros; Valente, Sergio; Mai, Antonello; Brancolini, Claudio; Giampietri, Claudia; Magenta, Alessandra; et al.
Abstract: Background: Histone deacetylase 4 (HDAC4) is a stress‐responsive factor that mediates multiple cellular responses. As a member of class IIa HDACs, HDAC4 shuttles between the nucleus and the cytoplasm; however, HDAC4 cytoplasmic functions have never been fully investigated. Duchenne muscular dystrophy (DMD) is a genetic, progressive, incurable disorder, characterized by muscle wasting, which can be treated with the unspecific inhibition of HDACs, despite this approach being only partially effective. More efficient strategies may be proposed for DMD only after the different HDAC members will be characterized. Methods: To fully understand HDAC4 functions, we generated dystrophic mice carrying a skeletal muscle‐specific deletion of HDAC4 (mdx;KO mice). The progression of muscular dystrophy was characterized in mdx and age‐matched mdx;KO mice by means of histological, molecular, and functional analyses. Satellite cells (SCs) from these mice were differentiated in vitro, to identify HDAC4 intrinsic functions influencing the myogenic potential of dystrophic SCs. Gain‐of‐function experiments revealed the cytoplasmic functions of HDAC4 in mdx;KO muscles. Results: Histone deacetylase 4 increased in the skeletal muscles of mdx mice (~3‐fold; P  < 0.05) and of DMD patients ( n  = 3, males, mean age 13.3 ± 1.5 years), suggesting that HDAC4 has a role in DMD. Its deletion in skeletal muscles importantly worsens the pathological features of DMD, leading to greater muscle fragility and degeneration over time. Additionally, it impairs SC survival, myogenic potential, and muscle regeneration, ultimately compromising muscle function ( P  < 0.05–0.001). The impaired membrane repair mechanism in muscles and SCs accounts for the mdx;KO phenotype. Indeed, the ectopic expression of Trim72, a major player in the membrane repair mechanism, prevents SC death (~20%; P  < 0.01) and increases myogenic fusion (~40%; P  < 0.01) in vitro ; in vivo it significantly reduces myofibre damage (~10%; P  < 0.005) and improves mdx;KO muscle function ( P  < 0.05). The mdx;KO phenotype is also fully rescued by restoring cytoplasmic levels of HDAC4, both in vitro and in vivo . The protective role of HDAC4 in the cytoplasm of mdx;KO muscles is, in part, independent of its deacetylase activity. HDAC4 expression correlates with Trim72 mRNA levels; furthermore, Trim72 mRNA decays more rapidly ( P  < 0.01) in mdx;KO muscle cells, compared with mdx ones. Conclusions: Histone deacetylase 4 performs crucial functions in the cytoplasm of dystrophic muscles, by mediating the muscle repair response to damage, an important role in ensuring muscle homeostasis, probably by stabilizing Trim72 mRNA. Consequently, the cytoplasmic functions of HDAC4 should be stimulated rather than inhibited in muscular dystrophy treatments, a fact to be considered in future therapeutic approaches.